(untitled) (Journal of Applied Learning and Teaching, 2025)
This study examines the way artificial intelligence (AI) impacts critical thinking among Iranian university students in relation to the ways in which it may either promote or inhibit cognitive involvement, focusing specifically on these factors. Using a mixed methods approach, the study collected responses from 348 students using questionnaires and interviewed students in greater depth to explore their perceptions of AI in decision-making, problem-solving, and bias awareness. The findings showed that students are very worried about relying too much on AI. The students who answered the survey felt that AI made them less independent or critical in their thinking, more comfortable with automation, and more biased by algorithms. Still, everyone agrees that AI literacy should be taught in universities so that students can think critically about the information AI gives them and avoid being biased. This will help with balanced cognitive engagement. This study argues that while AI can enhance decision-making, its associated dangerous effects must be managed via ethical development, education reforms, and lifelong learning initiatives to present AI as a friend of critical thinking rather than a threat.